2022
DOI: 10.38001/ijlsb.1085539
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antibacterial, Antioxidant and DNA Damage Protective Activity of Blackberry (Rubus fruticosus L.) Root Extracts

Abstract: The aim of this study is to explore the antibacterial, antioxidant, and DNA damage protection potentials of blackberry (Rubus fruticosus L) root extracts. Antioxidant activity of root extracts was researched by using DPPH˙ free radical scavenging and reducing capacity analysis. Methanolic extract of blackberry root system showed the maximum activity for TPC, TFC, DPPH˙, and ferric reducing capacity. Antibacterial activity of blackberry root extracts was screened against clinic isolates (Escherichia coli, Klebs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Despite a dosage of 100 mg/mL, methanolic extract exhibited strong antibacterial activity. These outcomes showed that the antioxidant compounds found in blackberry root system extract (Rubus fruticosus L) is able to counteract the negative effects of free radical (27).…”
Section: Dna Damage Protectivementioning
confidence: 98%
“…Despite a dosage of 100 mg/mL, methanolic extract exhibited strong antibacterial activity. These outcomes showed that the antioxidant compounds found in blackberry root system extract (Rubus fruticosus L) is able to counteract the negative effects of free radical (27).…”
Section: Dna Damage Protectivementioning
confidence: 98%